An Empirical Analysis of Regulatory Risk in the Banking Industry - Karletides, GK (2018)
The following study investigates whether Enforcement Actions placed on banks for misbehaving, have a significant effect on their Cumulative Abnormal Returns or not. Considering a sample of 103 US Canadian banks for the period 2010-2018, I have observed that such actions levied by the Federal Deposit Insurance Corporation, the Office of the Comptroller of the Currency and the National Credit Union Administration will lead to a significant reduction in the share price of banks. Utilising a regression, I have provided evidence that the severity and type of enforcement actions will not play a major role in the abnormal returns of banks however, several banks characteristics will be the main determinants whether those banks will be affected from the enforcement actions or not. The results of this study present significant insights regarding the effects of EAs, which mostly agree with previous literature that suggests that the actions levied on banks will reduce the returns of banks leading to the formation of some issues. Finally, it can be observed that, in this study severe actions such as Cease, and Desists Orders, Prompt Corrective Actions and Formal Agreements/ Consent Orders dominate the observations number since the data range is placed just after the crisis where actions taken to prevent misconduct were much more severe and larger in number.